1981
DOI: 10.1037/0021-843x.90.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotically induced limb anesthesia and adaptation to displacing prisms: A failure to confirm.

Abstract: Three groups of subjects were tested for accuracy of pointing at a visual target before and after wearing displacing prisms. One group consisted of 10 highly susceptible subjects given a hypnotic suggestion for limb anesthesia following the pretest, and a second group included 10 low susceptible subjects instructed to fake limb anesthesia. A control group (n = 10) unselected on susceptibility received no special instructions. The high susceptibles reported significantly greater felt anesthesia than subjects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
2
18
2
Order By: Relevance
“…A portion of their adaptation magnitude may have been artifactual. Spanos et al (1981Spanos et al ( , 1983) also confirmed (and statistically so) the fmding first reported by our laboratory that the presence of hypnotic anesthesia is related to a failure to perform the nose-touch task in a veridical manner. Unlike the reports of Spanos et al, all of whose anesthetized subjects failed to accurately fmd their noses, we find either what Spanos et al reported or that subjects do find their noses but that it takes them longer to do so when their limbs are anesthetized than when they are not.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…A portion of their adaptation magnitude may have been artifactual. Spanos et al (1981Spanos et al ( , 1983) also confirmed (and statistically so) the fmding first reported by our laboratory that the presence of hypnotic anesthesia is related to a failure to perform the nose-touch task in a veridical manner. Unlike the reports of Spanos et al, all of whose anesthetized subjects failed to accurately fmd their noses, we find either what Spanos et al reported or that subjects do find their noses but that it takes them longer to do so when their limbs are anesthetized than when they are not.…”
Section: Discussionsupporting
confidence: 70%
“…We have argued that such anesthesia disrupts proprioceptive feedback from the arm and, as a result, adaptation does not occur (e.g., Wallace & Fisher, 1979). Spanos et al (1981) failed to replicate our effect; that is, they reported that adaptation to prism displacement occurs regardless of whether subjects are asked to perform a task with hypnotic anesthesia in the adapting limb or without it. However, as we have previously argued (Wallace & Fisher, 1982), Spanos et al (1981) introduced a situation during prism exposure that overrode the effect of the hypnotic anesthesia.…”
contrasting
confidence: 41%
See 3 more Smart Citations